Subclinical hyperthyroidism seems not to have a significant impact on systemic anticoagulation in patients with coumarin therapy - Bucerius, Jan; Naubereit, Anna; Joe, Alexius Y.; Ezziddin, Samer; Biermann, Kim; Risse, Jörn; Palmedo, Holger; Oldenburg, Johannes; Biersack, Hans-Jürgen (Thrombosis and Haemostasis, 2008)
There is little data regarding the impact of subclinical hyperthyroidism on coagulation metabolism in patients undergoing systemic anticoagulation therapy with coumarin derivates. In this retrospective analysis we studied 233 patients with benign thyroid disorders receiving therapeutic iodine-131, as well as concomitant systemic anticoagulation therapy (subclinical hyperthyroidism: n=178; overt hyperthyroidism: n=15; euthyroidism: n=40). Multivariate regression analyses were performed in the total study population as well as in the subgroup of patients with subclinical hyperthyroidism to identify the possible impact of several variables on anticoagulation therapy, large enough to push the International Normalized Ratio (INR) level out of the therapeutic range (INR <2.0 or >3.0).Therapy with antibiotics or nitrates was significantly associated with INR-values >3.0 in the total population, while ACE inhibitors were associated with lower incidence of INR-values <2.0. In patients with subclinical hyperthyroidism, therapy with antibiotics was predictive of INR-values >3.0, whereas therapy with thyroid suppressive drugs or TSH-values <0.1 mU/l was associated with INR-values <2.0. Moreover, in a subgroup of 40 patients with the positive history of both subclinical hyperthyroidism and euthyroidism intraindividual comparison with regard to the possible impact on anticoagulation therapy was performed which failed to show any significant differences in INR-values between the two thyroid metabolic conditions. In conclusion, subclinical hyperthyroidism seems to have no significant impact on coagulation metabolism in patients receiving anticoagulation therapy.
Keywords: Subclinical hyperthyroidism; anticoagulation therapy; coumarin derivates; benign thyroid disorders